A multicenter study of 30 days complications after deceased donor liver transplantation in the model for end‐stage liver disease score era. Issue 9 (25th August 2015) - Parikh, Anup; Washburn, Kenneth W.; Matsuoka, Lea; Pandit, Urvashi; Kim, Jennifer E.; Almeda, Jose; Mora‐Esteves, Cesar; Halff, Glenn; Genyk, Yuri; Holland, Bart; Wilson, Dorian J.; Sher, Linda; et al.
<x xml:space="preserve">Abstract</x> Knowledge of risk factors for posttransplant complications is likely to improve patient outcomes. Few large studies of all early postoperative complications after deceased donor liver transplantation (DDLT) exist. Therefore, we conducted a retrospective, cohort study of 30‐day complications, their risk factors, and the impact on outcomes after DDLT. Three centers contributed data for 450 DDLTs performed from January 2005 through December 2009. Data included donor, recipient, transplant, and outcome variables. All 30‐day postoperative complications were graded by the Clavien‐Dindo system. Complications per patient and severe (≥ grade III) complications were primary outcomes. Death within 30 days, complication occurrence, length of stay (LOS), and graft and patient survival were secondary outcomes. Multivariate associations of risk factors with complications and complications with LOS, graft survival, and patient survival were examined. Mean number of complications/patient was 3.3 ± 3.9. At least 1 complication occurred in 79.3%, and severe complications occurred in 62.8% of recipients. Mean LOS was 16.2 ± 22.9 days. Graft and patient survival rates were 84% and 86%, respectively, at 1 year and 74% and 76%, respectively, at 3 years. Hospitalization, critical care, ventilatory support, and renal replacement therapy before transplant and transfusions during transplant were the significant predictors of complications (not the Model for End‐Stage Liver Disease score). Both number and severity of complications had a significant impact on LOS and graft and patient survival. Structured reporting of risk‐adjusted complications rates after DDLT is likely to improve patient care and transplant center benchmarking. Despite the accomplished reductions in transfusions during DDLT, opportunities exist for further reductions. With increasing transplantation of sicker patients, reduction in complications would require multidisciplinary efforts and institutional commitment. Pretransplant risk characteristics for complications must factor in during payer contracting. Liver Transpl 21:1160‐1168, 2015. © 2015 AASLD.